Memahami Hermeneutika dalam Mengkaji teks Al-Qur’an - Rini Fitria (Alhadharah: Jurnal Ilmu Dakwah, 2016)
Fakultas Ushuluddin Adab dan Dakwah IAIN BengkuluThis paper contains about how to understand that critical hermeneutics originally began the study of philosophy towards the understanding of science communication or broadcast communication texts of Islam to understand the Qur'an. Theoretical, philosophical hermeneutics and critical hermeneutics is the science of how to interpret the meaning in the text with the study of the initiators, the reader and the context at the time. Al-Qur'an is a holy book that can be understood by assuming the critical hermeneutics, the word of Allah is understood by the readers of these words by looking asbabunnuzulul Qur'an.Keywords: hermenutika, Quran, initiators, reader and context